The Subjectivity of the Grading Evaluation System in the Religious Class in Greece - A New Approach - Zaviš Monika; Diamantopoulos Konstantinos A. (Sciendo, 2024)
Introduction: The grading process in secondary education is always challenging to navigate since the subjective dimension of the human parameter always seems to interfere dynamically in combination with the variety of the submitted assessment questions grounded on the grading teacher's style. The central questions asked are: a) what are the applied assessment styles among Greek Religious Education (RE) teachers? b) What are their main assessment criteria? Moreover, c) What kind of evaluation plans are used to benefit the students? The above assessment issue is affected by the culture and mentality of each teacher.